2020
DOI: 10.1136/bjophthalmol-2020-316105
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitudes and eye health-seeking behaviours in a population-based sample of people with diabetes in rural China

Abstract: AimsTo assess knowledge of diabetes and acceptance of eye care among people with diabetes in rural China, to improve service uptake.MethodsPopulation-based study of people in Guangdong, China, with glycosylated haemoglobin A1c≥6.5% and/or known history of diabetes. Between August and November 2014, participants answered a questionnaire (based on Delphi process/previous focus groups) on medical history, demographic characteristics, self-rated health and vision, knowledge about diabetes and diabetic retinopathy,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 29 publications
1
12
0
Order By: Relevance
“…Participants' knowledge of cataracts was assessed using eight questions in our study. Following the literature ( 15 , 20 ), these questions were developed by a group of health experts from Shaanxi Normal University and Zhongshan Ophthalmic Center (an authoritative ophthalmology institution in China). Each item was equally weighted.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Participants' knowledge of cataracts was assessed using eight questions in our study. Following the literature ( 15 , 20 ), these questions were developed by a group of health experts from Shaanxi Normal University and Zhongshan Ophthalmic Center (an authoritative ophthalmology institution in China). Each item was equally weighted.…”
Section: Methodsmentioning
confidence: 99%
“…The main barrier to the cataract surgery rate may come from the demand side, especially patients' knowledge of cataracts ( 15 , 16 ). In China, villagers can reduce at least 50% cost of cataract surgery through the New Rural Cooperative Medical System ( 17 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, our results suggest that all VDs knew that the New Cooperative Medical System covers cataract surgery, but only 54% of residents knew this. Studies showed that enriching eye-related knowledge could improve eye screening [ 34 , 35 ]. In rural areas, VDs are trusted by villagers and are always the first choice for seeking health services [ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, there might still be enormous unmet needs for eye care in the oldest-old Chinese adults, mainly due to a lack of awareness regarding preventable vision impairment and barriers to eye care services such as mobility problems and travel inconvenience [29,30]. Given that the number of older people with glaucoma and cataracts might continue to increase, eye care education for both oldest-old individuals and their families, as well as targeted interventions including early detection and timely treatment, are crucial for slowing eye diseases process to vision impairment [2,[31][32][33][34].…”
Section: Discussionmentioning
confidence: 99%